2022
DOI: 10.4081/monaldi.2022.2062
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ivermectin on non-severe and severe COVID-19 disease and gender-based difference of its effectiveness

Abstract: The COVID-19 pandemic has led to mortality and morbidity since December 2019. Many possible treatment options have been advised till date. The role of ivermectin in the treatment of COVID-19 disease remains controversial. The aim of our study was to evaluate the effect of ivermectin in hospitalized patients with non-severe and severe COVID-19 disease. We conducted a retrospective cohort study that compared outcomes in 2 groups of COVID-19 patients hospitalized at the largest tertiary care center of Pakistan. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Egypt The effect of ivermectin on non-severe and severe COVID-19 disease and gender-based difference of its effectiveness. Zubair et al, 2022 Pakistan…”
Section: Shoumann Et Al 2021mentioning
confidence: 99%
See 2 more Smart Citations
“…Egypt The effect of ivermectin on non-severe and severe COVID-19 disease and gender-based difference of its effectiveness. Zubair et al, 2022 Pakistan…”
Section: Shoumann Et Al 2021mentioning
confidence: 99%
“…Over 40 peer-reviewed studies ( Table 1 ) have demonstrated studies on the effectiveness of IVM in SARS-CoV-2 infection ( Alam et al, 2020 ; Khan et al, 2020 ; Kishoria et al, 2020 ; Reaz et al, 2020 ; Abd-Elsalam et al, 2021 ; Ahmed et al, 2021 ; Ahsan et al, 2021 ; Aref et al, 2021 ; Behera et al, 2021 ; Cadegiani et al, 2021 ; Chaccour et al, 2021 ; Chahla et al, 2021 ; Chowdhury et al, 2021 ; Elalfy et al, 2021 ; Faisal et al, 2021 ; Ferreira et al, 2021 ; Hellwig and Maia, 2021 ; Krolewiecki et al, 2021 ; Lima-Morales et al, 2021 ; López-Medina et al, 2021 ; Mohan et al, 2021 ; Morgenstern et al, 2021 ; Mukarram, 2021 ; Okumuş et al, 2021 ; Podder et al, 2021 ; Rajter et al, 2021 ; Ravikirti et al, 2021 ; Rezk et al, 2021 ; Seet et al, 2021 ; Shahbaznejad et al, 2021 ; Shoumann et al, 2021 ; Abbas et al, 2022 ; Ascencio-Montiel et al, 2022 ; Babalola et al, 2022 ; Beltran Gonzalez et al, 2022 ; Buonfrate et al, 2022 ; Hazan et al, 2022a ; Kerr et al, 2022 ; Lim et al, 2022 ; Mayer et al, 2022 ; Mustafa et al, 2022 ; Ozer et al, 2022 ; Reis et al, 2022 ; Shimizu et al, 2022 ; Zubair et al, 2022 ), with over 80% of studies showing positive outcomes with IVM treatment. Overall, IVM has shown 60–85% improvement in outcomes, including mortality, ventilation, recovery, clearance, and hospital/ICU admissions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides, an Egyptian study observed a decreased in IL-6 and IL-1 cytokines in COVID-19 patients treated with IVM, with a reduction in the mortality rate and the hospitalization time [ 251 ]. Conversely, studies conducted in Pakistan and China did not detect differences in mortality rate, inflammatory markers, time of hospitalization, time of resolution of symptoms and syndrome course in mild and severe COVID-19 subjects [ 252 , 253 ]. Likewise, an American prospective study on 286 patients treated with two doses of IVM found no benefits in hospitalization time, intensive care unit admission, intubation rate or mortality [ 254 ].…”
Section: Anthelmintic Drugs Against Sars-cov-2mentioning
confidence: 99%